2017
DOI: 10.1016/j.jaad.2017.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular comorbidities of pediatric psoriasis among hospitalized children in the United States

Abstract: Pediatric psoriasis is associated with higher odds of multiple cardiovascular comorbidities among hospitalized patients. Strategies for mitigating excess cardiovascular risk in pediatric psoriasis need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 16 publications
3
33
1
5
Order By: Relevance
“…In the current study, we found a higher prevalence of overweight/obesity in children with psoriasis (27.4%) than controls (12.4%) with OR 2.67, which are consistent with findings of the studies conducted by Kwa et al . (only obese) 7.4% versus 1.5%, Boccardi et al . (only overweight) 48.0% versus 27.0%, Zhu et al .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In the current study, we found a higher prevalence of overweight/obesity in children with psoriasis (27.4%) than controls (12.4%) with OR 2.67, which are consistent with findings of the studies conducted by Kwa et al . (only obese) 7.4% versus 1.5%, Boccardi et al . (only overweight) 48.0% versus 27.0%, Zhu et al .…”
Section: Discussionmentioning
confidence: 90%
“…Only one child in the control group had hypertension. Similar findings were identified by Kwa et al ., 4.2% versus 1.2%, and Torres et al ., 10.0% versus 3.7% …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations